Differences in Diet and Gut Microbiota Between Lactating and Non-lactating Asian Particolored Bats (Vespertilio sinensis): Implication for a Connection Between Diet and Gut Microbiota - Li, Jingjing; Chu, Yujia; Yao, Wenwen; Wu, Hui; Feng, Jiang (Frontiers in Microbiology, 2021)
In mammals, lactation is considered the most energetically costly phase for females. To meet nutritional and energy demands, lactating females usually change feeding patterns by eating food that is higher in protein and calories. Their gut microbes respond accordingly to help adapt to the changes in diet. In this study, we examined differences in diet and gut microbial composition between lactating and non-lactating Asian particolored bats (Vespertilio sinensis) using COI and 16S amplicon sequencing. When compared with non-lactating bats, we found that the diversity and composition of lactating bats’ diets differed; the proportion of Diptera increased and Coleoptera and Orthoptera decreased significantly. This could be attributed to the easy availability and high protein content of Diptera. Comparative analysis of the gut microbiota of lactating and non-lactating females showed that although the diversity of gut microbiota did not change, the relative abundance of specific gut microbiota associated with a particular diet did change. For example, when the consumption of Coleoptera decreased in lactating bats, the relative abundance of Lactobacillaceae was also reduced. Lactobacillaceae are thought to be involved in the digestion of Coleopteran exoskeletons. This study suggests that during lactation, Asian particolored bats eat a diet that yields higher levels of protein, and at the same time, the abundance of specific gut microbes change to help their hosts adapt to these changes in diet.